THE PLACE OF BALLETMEISTER ART IN EUROPEAN COUNTRIES - Pirlepesova Zibash Umirzakovna (Web of Journals Publishing, 2025)
This article explores the formation, development, and modern significance of ballet master art in European countries. Ballet master art is an integral part of European cultural heritage, with its influence vividly manifested in the development of ballet dramaturgy, dance techniques, and stage art. The article highlights the historical significance of ballet mastery in various European countries, its modern interpretations, and its role in strengthening cultural harmony.
Keywords: Ballet master, European art, ballet history, dramaturgy, dance techniques, cultural heritage, contemporary ballet.